Science, reading, and Renaissance literature : the art of making knowledge, 1580-1670 - Spiller, Elizabeth (Cambridge studies in Renaissance literature and culture ;, 2004)
Brings together key works in early modern science and literature (from the anatomy of William Harvey and the experimentalism of William Gilbert to the fictions of Philip Sidney, Edmund Spenser, and Margaret Cavendish) to explore how two cultures and disciplines, science and literature, developed through a shared aesthetic of knowledge.